Application of Complementary Therapy of Warm Compress with Boiled Ginger Water to Reduce Pain in Mr. S's Family, Especially the Elderly Mrs. S with Osteoarthritis in Perum Puspa Raya RT 002 RW 012 Kel Bojong Baru, Kec Bojong Gede, Bogor Regency, West Java - Dayuningsih, Dayuningsih (JOURNAL EDUCATIONAL OF NURSING(JEN), 2021)
Elderly is someone who is over 60 years old. And the elderly will experience changes such as physical, psychological and psychosocial changes. There are several disorders that are commonly found in the elderly process, one of which is joint disorders such as osteoarthritis. Osteoarthritis is a chronic degenerative disease that is widely suffered by elderly adults and is characterized by damage to the cartilage in the joints. The purpose of this family nursing care is to help families overcome osteoarthritis problems independently by applying complementary therapy of warm compresses with boiled ginger water to reduce pain. One of the families targeted for family nursing care is Mr. S, especially the elderly Mrs. S with osteoarthritis. After the assessment, it was found that the nursing diagnosis of family nursing management was ineffective. Furthermore, the action was taken, namely the application of complementary therapy of warm compresses with boiled ginger water for 5 consecutive days and there was a decrease in pain. The last step was to evaluate the problem, TUK 1, TUK 2 were achieved and in TUK 3, TUK 4, TUK 5 had not been achieved so that follow-up was needed to overcome the problem. The writing method used is descriptive with a case study approach where the author took one of the families given care by applying complementary therapy of warm compresses boiled with ginger water. The application of complementary therapy of warm compresses boiled with ginger water has been proven to be able to reduce pain in families with osteoarthritis problems, although the results are not significant because they are only carried out for 5 consecutive days.